A CONSTRUCTION CONTRACT AS A REGULATOR OF RELATIONS IN A CONSTRUCTION SPHERE - Слободська, Ірина Андріївна; Стешенко, Марина Віталіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to explore the legal nature of contractual relations in the construction industry. Methods of research: general and special methods of knowledge of legal phenomena were used in the work. In particular, the application of the system-functional method helped to determine the functional purpose of the contract of construction contract. Using the formal-dogmatic method of research, the most important legal constructs of the contract of construction contract were identified. The comparative-legal method was used when comparing the normative-legal acts of Ukraine and foreign legislation in the sphere of regulation of contractual relations by state order. Results: the ways of improving the legal regulation of contractual relations in construction were determined, the content of contractual relations in the construction industry was analyzed. Discussion: modern market relations in the construction industry cannot be imagined without a contract, because the shortcomings of the contractual regulation reduce the ability to protect the rights of the contracting party. The economic necessity and legal complexity of the construction contract with its complex system of contractual relations, necessitates its detailed legal regulation. The problems of normative-legal regulation and practice of application of the contract of construction contract were justified by the rapid development of the construction industry. It is determined that the contract of construction contract means the contract, by virtue of which the contractor undertakes the obligation to perform the construction works specified in the contract within the term specified by the contract, and the customer is obliged to accept the result of the works, to pay for it, and to create the contractor necessary for the execution of the works conditions in accordance with the terms of the contract. It is obvious that the regulatory and legal aspects of the industry require a systematic and perfect scheme for managing the situations that arise during the activity. It is stated that today it is necessary to create conditions for the use of internationally recognized forms of construction contracts, international customs, recommendations of international organizations as mechanisms for overcoming the defects of legal regulation of contractual relations in construction. Today, the legislation does not impose specific requirements on the contracting authority (such activity is not subject to licensing or certification), but at the same time it imposes serious powers on it and places fairly rigid liability. However, this situation can be remedied by improving the term «construction contractor» in Ukrainian legislation and forming a clear definition and systematization of the construction contractor’s functions with a division into their own functions and those that can be delegated. The problems and risks involved in the implementation of construction contracts in Ukraine remain an open question in the current state of the country.